2010
DOI: 10.1371/journal.pone.0012906
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Mediates the Response of Epithelial and Stromal Cells to Lipopolysaccharide in the Endometrium

Abstract: BackgroundAscending infections of the female genital tract with bacteria causes pelvic inflammatory disease (PID), preterm labour and infertility. Lipopolysaccharide (LPS) is the main component of the cell wall of Gram-negative bacteria. Innate immunity relies on the detection of LPS by Toll-like receptor 4 (TLR4) on host cells. Binding of LPS to TLR4 on immune cells stimulates secretion of pro-inflammatory cytokines such as IL-6, chemokines such as CXCL1 and CCL20, and prostaglandin E2. The present study test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 34 publications
5
63
1
2
Order By: Relevance
“…The interaction between LPS and TLR4 results in the activation of intracellular signaling through myeloid differentiation factor 88 (MyD88) and TIR-domain-containing adapter-inducing interferon-β (TRIF) pathways, leading to the activation of major mitogen-activated protein kinases (MAPKs) and translocation of nuclear transcription factor-κB (NF-κB) (Sheldon and Roberts, 2010;Kawai and Akira, 2011;Huang et al, 2016). NF-κB regulates the expression of cytokines, including interleukin (IL)-1β, IL-6, IL-8, and tumor necrosis factor-α (TNF-α), which are essential mediators of the inflammation response (Wang et al, 2012;Liu et al, 2014;Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between LPS and TLR4 results in the activation of intracellular signaling through myeloid differentiation factor 88 (MyD88) and TIR-domain-containing adapter-inducing interferon-β (TRIF) pathways, leading to the activation of major mitogen-activated protein kinases (MAPKs) and translocation of nuclear transcription factor-κB (NF-κB) (Sheldon and Roberts, 2010;Kawai and Akira, 2011;Huang et al, 2016). NF-κB regulates the expression of cytokines, including interleukin (IL)-1β, IL-6, IL-8, and tumor necrosis factor-α (TNF-α), which are essential mediators of the inflammation response (Wang et al, 2012;Liu et al, 2014;Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies investigated the interactions between LPS and bovine endometrial cells (EECs) (Herath et al, 2009;Sheldon and Roberts, 2010), the signaling molecules of the TLR4 signaling pathway in bovine hepatocytes have not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that altered expression and production of pro-inflammatory cytokines postpartum could contribute to impaired inflammatory response and predispose cows to development of metritis. (52). They created mutant mice lacking TLR4 and showed that intrauterine infusion of purified LPS induced an inflammatory response with accumulation of granulocytes throughout the endometrium of wild type (WT) but not Tlr4(-/-) mice.…”
Section: Mechanism Of Recognition Of Pathogens By Professional Phagocmentioning
confidence: 99%